2021
DOI: 10.1055/s-0041-1730925
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Alveolar Echinococcosis

Abstract: Hepatic alveolar echinococcosis (HAE) is a rare but severe zoonosis caused by the pseudotumoral intrahepatic development of the larval stage of the tapeworm Echinococcus multilocularis. HAE is present only in the Northern Hemisphere, predominantly in China. Currently, there is a significant resurgence of cases in historically endemic areas associated with emergence of HAE in countries not previously concerned. Today, in European countries, HAE is often discovered by chance; however, clinicians should be made a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 121 publications
0
26
0
1
Order By: Relevance
“…Once diagnosed, every patient mandatorily receives a parasitostatic pharmacotherapy with benzimidazole derivatives (BMZ), preferably albendazole. If possible, complete surgical removal of the parasitic lesions or metacestode tissue plus temporary adjuvant pharmacotherapy is the treatment of choice [8,10], while lifelong parasitostatic pharmacotherapy with BMZ alone offers an alternative if surgery is infeasible [11,12]. Therapeutic success is again assessed using imaging and laboratory procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Once diagnosed, every patient mandatorily receives a parasitostatic pharmacotherapy with benzimidazole derivatives (BMZ), preferably albendazole. If possible, complete surgical removal of the parasitic lesions or metacestode tissue plus temporary adjuvant pharmacotherapy is the treatment of choice [8,10], while lifelong parasitostatic pharmacotherapy with BMZ alone offers an alternative if surgery is infeasible [11,12]. Therapeutic success is again assessed using imaging and laboratory procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Given the infectious nature of the disease and the high risk of metastatic disease progression on immunosuppression, clinicians are reluctant to list these patients for transplantation early in the course of disease. Bresson-Hadni et al reported that the number of patients that underwent LT for AE is decreasing due to the better understanding of medical, surgical and interventional treatment [47].…”
Section: Discussionmentioning
confidence: 99%
“…The PNM categorization system denotes the presence of a parasite mass in the hepatic artery (P), the involvement of surrounding organs (N), and the involvement of distant sites (M). The goal of the PNM classification system is to improve the quality of service and to allow for consistent outcome evaluation across healthcare institutions [5]. An important role for radiologists is to ensure timely referral to specialists and imaging follow-up; but because AE imaging features are so variable, initial misdiagnosis is common, especially in nonendemic areas.…”
Section: Introductionmentioning
confidence: 99%